TRADITIONAL KNOWLEDGE OF MEDICINAL PLANTS USED BY PALIYANS AND PULIYANS IN PACHALUR AND PERIYUR HAMLETS, DINDUGAL DISTRICT, TAMIL NADU. - R.PRADEEP KUMAR; SRISAKTHI; JOSEPH JOHN (International Journal of Pharma and Bio Sciences, 2015)
An ethnobotanical survey was carried out among the ethnic groups’ of paliyans and puliyans in pachalur and periyur hamlets, Dindugal district, Tamil nadu. The tribal communities of paliyans and puliyans nurture rich knowledge about medicinal plants and its uses. Therefore, an exhaustive ethnomedicinal survey in this area. In this present investigation, it is observed that 19 species of plants included in 16 families have been recorded which are being potentially exploited by the tribal groups in curing different human ailments like wound healing, cold, tooth ache, jaundice, dysentry, asthma, bronchitis,etc.